2018
DOI: 10.1038/s41388-018-0509-4
|View full text |Cite
|
Sign up to set email alerts
|

ZNF185 is a p63 target gene critical for epidermal differentiation and squamous cell carcinoma development

Abstract: Development and maintenance of healthy stratified epithelia require the coordination of complex transcriptional programmes. The transcription factor p63, a member of the p53 family, plays a crucial role in epithelial development and homeostasis. Analysis of the p63-dependent transcriptome indicated that one important aspect of p63 functions in epithelial development is the regulation of cell–cell and cell–matrix adhesion programmes. However, limited knowledge exists on the relevant cell–cell adhesion molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…We have previously shown that the p53 family member p63, using a novel promoter region and a specific enhancer, directly regulated ZNF185 expression in keratinocytes [33]. To investigate whether also p53 could regulate ZNF185 expression and expand the p53 target genes involved in cytoskeleton regulation and cell polarity, we further analysed ZNF185 promoter region using UCSC genome browser (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the p53 family member p63, using a novel promoter region and a specific enhancer, directly regulated ZNF185 expression in keratinocytes [33]. To investigate whether also p53 could regulate ZNF185 expression and expand the p53 target genes involved in cytoskeleton regulation and cell polarity, we further analysed ZNF185 promoter region using UCSC genome browser (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…RNA sequencing was performed as previously described [95]. Briefly, total RNA was extracted using a mirVana miRNA isolation kit (Thermo Fisher).…”
Section: Methodsmentioning
confidence: 99%
“…The p63 protein also binds to the enhancer region of ZNF185 and promotes its expression in keratinocyte during epithelial differentiation. However, ZNF185 is downregulated in HNSCC, esophageal and cervical SCC even though p63 is commonly amplified in these cancers [ 27 ]. It is not clear why ZNF185 is decreased in SCC, and may be due to loss of function mutations on coactivators bound to p63, which results in a decrease of enhancer activity of ZNF185 in SCC cells.…”
Section: Tp63 Establishes a Squamous Subtype-specific Enhancer Landscmentioning
confidence: 99%
“…ΔNp63α is the prominent isoform of the TP63 gene expressed in keratinocytes and basal cells of diverse epithelia [ 19 21 ] and various SCCs [ 2 ]. ΔNp63α promotes SCC development through regulating different target genes, including cell growth and proliferation [ 22 , 23 ], extracellular matrix (ECM)–receptor interaction [ 24 ], cell adhesion [ 25 27 ], glucose metabolism [ 28 , 29 ], anti-oxidant defense [ 30 , 31 ], DNA damage repair [ 32 , 33 ], terminal differentiation [ 34 , 35 ], and inflammation and angiogenesis [ 36 41 ] (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%